(untitled) (REMUNOM, 2024)
The present work is a research that addresses the legal evolution of the protection of the indigenous population, with regard to Brazilian history, since the arrival of the Portuguese in Brazil, in 1500, until the present day, demonstrating that there has not yet been an appreciation for their protection, especially with regard to the rights to demarcate indigenous lands. This research discusses how, after the promulgation of the 1988 Federal Constitution, this population achieved great victories in terms of protection and guarantees to remain as indigenous people, continuing their origins and traditions, with the right to demarcate their stolen goods. lands. with time. However, even so, there is no defined line on how this land demarcation will be carried out, in a way that guarantees balance between the different indigenous tribes and the owners of the demarcated lands. In fact, this is the great debate of discussions between the Brazilian National Congress and the Federal Supreme Court, culminating to this day in the regulation of article 231 of the Federal Constitution of 1988, through Law 14,701, of 10/20/2023 to provide for the demarcation , the use and management of indigenous lands, this research sought to discuss, as recognized by the 1988 Constitution, that the rights acquired by indigenous peoples in Brazil cannot be withdrawn or revised.